Pandangan Ekonomi Islam Terhadap Praktek Gadai Lahan Sawit Di Desa Pulo Bargot Kecamatan Marbau Kabupaten Labuhanbatu Utara - Yulianti, Marliyah, Tri Inda Fadhila Rahma (Education Achievement: Journal of Science and Research, 2022)
This research aims to find out the Islamic Economic view on the practice of palm oil pawns in Pulo Bargot Village, Merbau Subdistrict, North Labuhanbatu Regency. This type of research is qualitative using phenomenological and normative approaches. The source of the data in this study is the people who do pawns and religious figures. Data collection techniques use interviews, documentation and literature studies. The results showed that the implementation of oil palm land pawns that occurred in Pulo Bargot Village, Merbau Subdistrict, North Labuhanbatu Regency has not been in accordance with the element of help as explained in the principles of Islamic Economics that "The main driving force of Islamic Economy is cooperation," It contains an element of injustice among others. In the case of guaranteed goods, namely oil palm land, pawn practices that occur in Pulo Bargot Village, collateral goods are fully utilized by murtahin during the agreement period, while the murtahin party will also still get a full refund from rahin at maturity. Furthermore, the practice of pawning the oil palm land of Pulo Bargot Village that occurs includes unauthorized pawns, because the practice of pawns carried out can cause jahalah (unclear).